Boost Me: Prevalence and Reasons for the Use of Stimulant Containing Pre Workout Supplements Among Fitness Studio Visitors in Mainz (Germany) - Dreher, Matthias; Ehlert, Tobias; Simon, Perikles; Neuberger, Elmo W. I. (Frontiers in Psychology, 2018)
The rapidly increasing interest in fitness related sports over the past few years has been accompanied by a booming industry of nutritional supplements. Many of these substances have unproven benefits and are even potentially harmful to the user. The aim of this study was to determine the prevalence and reasons for nutritional supplement (NS) use among fitness studio visitors in Mainz (Germany), emphasizing new multi-ingredient based supplements such as pre workout boosters (PWBs). Some of the PWBs contain stimulants such as DMAA, N,α-DEPEA, DMAE and DMBA with so far unknown risks, harms and benefits. 492 participants in 13 fitness studios completed a self-created questionnaire on the use of nutritional supplements. Descriptive statistics and chi-square tests were used to examine differences in supplement use regarding training- and intake reasons. About 57% of the participants reported the use of NS during the last 4 weeks. The all-time prevalence of creatine use was 28.7%, whereas 12.2% of the participants stated creatine use during the past 4 weeks. The all-time prevalence of PWB intake was 25.8%, whereas the last month prevalence was 11.8%. Among the group of PWB users, 20.5% stated to search specifically for substances such as DMAA, N,α-DEPEA, DMAE or DMBA. Logistic regression analysis showed positive relations between creatine use and predictor variables gender, strength training and bodybuilding, as well as the stated exercisers’ training reasons to increase physical- and sports performance, and quality of life. PWB consumption was related to the variables gender, training frequency and the reason for sports performance enhancement. Specific ingredient focus was related to the predictor variables competition participation and increase of mental performance. The results of the study show a high prevalence of PWBs consumption among fitness studios visitors, which is comparable with creatine use. The predicting variables for consumption seem to be slightly different between the supplements, especially if the users are searching for stimulating agents. The current findings help to create preliminary consumption patterns and can help to identify potential endangered fitness studio visitors for prevention and risk communication, especially for PWBs.